만성 골수염이 동반된 후족부 난치성 궤양의 음압 창상 치료 및 임시 봉합술 병행 치료: 증례 보고 - 김지연; 윤종환; 강지훈; Jiyoun Kim; Jong Hwan Yun; Jihun Kang (대한족부족관절학회지, 2025)
The heel is the second most common area for pressure injuries, which can lead to serious and threatening extremity infections. The late stages of deep hindfoot ulcers, where osteomyelitis commonly coexists, can result in an extended therapeutic window. Standard treatments for hindfoot ulcers complicated by osteomyelitis encompass debridement and flap surgery. In severe cases, below-knee amputation is also considered. Recent studies have reported the efficacy of negative pressure wound therapy (NPWT) in addressing refractory foot ulcers. The authors developed a temporary tension suture (TTS) in combination with NPWT to shorten the treatment duration of refractory foot ulcers, providing additional appropriate tension for wound coverage. The authors report for the first time a case of a 73-year-old female patient who had been experiencing an intractable hindfoot ulcer with chronic osteomyelitis for 18 months. NPWT and TTSs were applied concurrently with favorable outcomes.